PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP KETERAMPILAN HANDSPRING - Turrahma, Alfia; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe development of learning models and methods provides great opportunities for educators for interesting learning. There are still many students who are not focused on learning, learning patterns are still needed for the teacher, and still do not provide a pattern of participation in accordance with the character of students. The purpose of this study was to study the effect of the investigation group learning model on handspring skills at SMP Negeri 21 East Pontianak.The method used in this study is research with an experimental pre-design form. The population in this study were students of class VIII in SMP Negeri 21 East Pontianak who collected 200 and the sample in this study were students of class AE who were involved in 40 with a purposive sample technique that is a sample technique with certain assistance, such as from the findings and testing of researchers do, students do not understand the handspring technique on gymnastics on the floor, many are afraid to try. Data analysis with computerized systems and analysis using t-test.The results of the study assessed the average pretest score of 50.05 and the average posttest score of 71.7. Data analysis obtained the value of the t-test with the difference in the value of the pretest and posttest was 21.65 then Ha was accepted to support or improve students' handspring skills in SMP Negeri 21 East Pontianak after being treated with the investigative group learning model and the effect size value obtained by 1, 78 included in the high category. Key words : Models, group investigations, handspring